Thermal effect mechanism of magnetoresistance p-type diamond films - 秦国平 孔春阳 阮海波 黄桂娟 崔玉亭 方亮 (Chinese physics B, 2010)
Based on the analysis and the discussion of the influence of thermal ionization energy and various scatterings on magnetoresistance（MR） of p-type diamond films, a revised model of valence band split-off over temperature is put forward, and a corresponding calculation formula is given for the MR of p-type diamond films （Corbino discs）. It is shown that the theoretical calculation that the MR of diamond films changes with temperature is consistent with the experiment. The influence of Fermi energy level on MR of diamond films is discussed. Additionally, the thermal effect mechanism of MR in p-type diamond films is also explored.